Effects of drying methods on chemical composition, antioxidant and antibacterial activities of torch ginger (Etlingera elatior Jack) flower extracts and essential oil - Anzian, Aliaa (2018)
Torch ginger (Etlingera elatior Jack) flower is a well-known spice for local delicacies and natural remedies that has been reported to possess significant antioxidant and antibacterial activities. However, the maturity stages, drying conditions and extraction methods are still questionable in preserving bioactive compounds of torch ginger flower. Therefore, the aims of this study were to profile the bioactive compounds in different maturity stages (tight bud and full bloom) of torch ginger flowers using Gas Chromatography-Mass spectrometry (GC-MS). Then, the effect of drying methods; freeze, oven and sun drying on extraction yield and antioxidant activities of selected maturity stage of torch ginger flowers were studied. Torch ginger flower’s essential oil extracted using subcritical carbon dioxide (SubC-CO2) were evaluated for antioxidant and antibacterial activities against selected foodborne pathogens, namely Bacillus cereus ATCC10876, Escherichia coli ATCC11229, Klebsiella pneumoniae ATCC13773, Listeria monocytogenes ATCC19111, Salmonella Typhimurium ATCC13311, and Staphylococcus aureus ATCC29213. Maturity stage had significant effect on percentage area of bioactive compounds concentrations (caryophyllene and 1- dodecanol) in torch ginger flower extract. Oven drying was identified as optimum extraction yield of 37.8±2.48% with high level of scavenging activity of 62.4±1.24% and IC50 value of 9.68 mg/mL, ferric reducing assay power of 2340.7±65.53 mg Fe2+/100 g, total phenols content of 331.6±2.85 mg GAE/100 g and total flavonoids of 465.8±2.08 mg QE/100 g. The antioxidant activities of torch ginger flower’s essential oil through DPPH assay (90.0±0.25%), FRAP assay= 8876.5±36.35, ABTS scavenging activity= 81.8±2.10%, TPC= 1590.2±3.74 mg GAE/100 g and TFC= 1686.2±17.34 mg QE/100 g. Minimal Inhibitory Concentration (MIC)= 1.56 mg/mL and Minimal Bactericidal Concentration (MBC)= 3.13 mg/mL of torch ginger flower’s essential oil were able to inhibit the growth of B. cereus and K. pneumoniae. This study clearly indicated that torch ginger flower could be potentially used as natural antioxidant and antibacterial agent in the food and pharmaceutical fields.